Avaliação e expressão da incerteza de medições oceanográficas em boias - Fragoso, Igor Afonso (2018)
The concept of measurement uncertainty considers as a result not a single value but an interval where the value of the measured quantity will be included with a specified degree of confidence. This definition then determines that uncertainty is always associated with a measurement and not only with its process, that is, every measurement has its respective uncertainty. The field of application of measurement uncertainty measurement and expression covers all measurement activities, from field or floor measurement to fundamental research, establishing procedures for this. The present work proposes its application in measurements made in the marine environment, based on data available to users, following the guidelines in the Guide to Expression of Uncertainty in Measurement (GUM). As an example, we evaluated the uncertainties of measurements made by PNBOIA and REMO meteo-oceanographic buoys of wind, waves and marine currents. These assessments have shown that the uncertainties associated with time series data are strongly influenced by their estimators and that studies on the subject are strongly recommended. The results obtained do not include all the sources of uncertainty that could impact the measured measurements, however, it is evidenced that the evaluation and expression of the uncertainty of the analyzed measurements, make the results more realistic.